Market Feasibility Study on "VNursLab" as a Nursing Learning Media - Putra, Muhammad Alfi Mahardika; Purnama, Dadang; Komariah, Maria (Journal of Nursing Care, 2023)
Background: Padjadjaran University innovates by presenting virtual reality technology as a new learning media. Virtual reality technology is presented under the name "VNursLab" in which there are interactive 3D modules and simulations of virtual nursing procedures that are made to resemble procedure experiences in the real world. A feasibility test on the "VNursLab" virtual reality product is required before the use of "VNursLab" as a learning media. Aim: This study aims to describe the potential use of virtual reality “VNursLab” as nursing learning media by conducting a feasibility study using marketing mix methods.Method: This research design is a descriptive quantitative study. The participant of this Research is representative of a nursing study institution participating in rapat tahunan anggota (RTA) of AIPNI region IV and total sampling as a sampling technique. The instrument used in this study was developed based on the marketing mix methods using 4 variables: Product, Price, Place, and Promotion.Result: The feasibility study result showed that VNursLab received good feedback from its respondent as one of the intended markets with all variables receiving scores higher than 51% of the Likert Score.Conclusion: Virtual reality “VNursLab” is feasible and has a good potential to be used as a new nursing learning method although it still needs some improvement.